2015
DOI: 10.18632/oncotarget.5826
|View full text |Cite
|
Sign up to set email alerts
|

Foxo3a-mediated overexpression of microRNA-622 suppresses tumor metastasis by repressing hypoxia-inducible factor-1α in erk-responsive lung cancer

Abstract: Metastatic spread of cancer cells portends a poor prognosis and mortality for lung cancer patients. Hypoxia-inducible factor-1α (HIF-1α) enhances tumor cell motility by activating the epithelial-to-mesenchymal transition (EMT), which is considered a prerequisite for metastasis. Recent studies of microRNA involvement in cancer invasion and metastasis have highlighted the role of such RNAs in tumor development. However, little work has been done to identify tumor suppressor microRNAs that target HIF-1α to down-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 42 publications
2
39
1
Order By: Relevance
“…Huang et al reported that activation of p53 and p21 was related to the inactivation of PI3K/AKT and ERK signaling pathways during virus replication [39]. PI3K/ AKT or MEK/ERK pathways, has been reported to control proliferation and differentiation of stem cells [26][27][28]. The present study suggests that Nap1l1 activates ERK or AKT pathway to promote the proliferation by downregulation of p21 and p27 and upregulation of cyclin B1 in iPSC.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Huang et al reported that activation of p53 and p21 was related to the inactivation of PI3K/AKT and ERK signaling pathways during virus replication [39]. PI3K/ AKT or MEK/ERK pathways, has been reported to control proliferation and differentiation of stem cells [26][27][28]. The present study suggests that Nap1l1 activates ERK or AKT pathway to promote the proliferation by downregulation of p21 and p27 and upregulation of cyclin B1 in iPSC.…”
Section: Discussionsupporting
confidence: 52%
“…Here, we used the U0126, a specific inhibitor of MEK, which can efficiently inhibit the MEK-mediated phosphorylation of ERK [27], to inhibit ERK activation as previous study [28], while MK2206 was used as the AKT inhibitor in the present study. The results showed that U0126 or MK2206 greatly reversed the proliferous effect induced by Nap1l1 overexpression in iPSC.…”
Section: Inhibition Of Akt or Erk Activation Greatly Reverses The Promentioning
confidence: 99%
“…In addition, the Erk signaling pathway has been shown to be frequently activated in numerous kinds of human cancers [43][44][45]. Aberrant activation of phosphorylated Erk1/2 induced by miRNAs has been observed in lung cancer [45][46][47]. Recent reports point out that miR-379 acts as a tumor [45], miR-7 inhibits the activation of ERK/MAPK signaling pathway by down-regulating FAK expression [46], and miR-622 overexpression decreases invasion in lung tumor cells by inhibiting HIF-1alpha via inactivation of ERK signaling in A549 cell [47].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant activation of phosphorylated Erk1/2 induced by miRNAs has been observed in lung cancer [45][46][47]. Recent reports point out that miR-379 acts as a tumor [45], miR-7 inhibits the activation of ERK/MAPK signaling pathway by down-regulating FAK expression [46], and miR-622 overexpression decreases invasion in lung tumor cells by inhibiting HIF-1alpha via inactivation of ERK signaling in A549 cell [47]. Consistent with these findings, we found that the p-Erk level was significantly decreased in response to GCNT3 silencing or miR-302b-3p overexpression in XWLC and NCI-H292 cells, suggesting that the effect of the miR-302b-3p/GCNT3 signaling pathway in NSCLC may depend on the activation of p-Erk.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence and metastasis are important causes of death in patients with endometrial cancer, and some studies have found that tumor invasion and metastasis are closely related to epithelial–mesenchymal transition (EMT) [26]. EMT is an intricate process where cancer cells demonstrate the loss of polarity and cell phenotype alteration from epithelial to mesenchymal morphology and it is considered a prerequisite for the typical tumor phenotypes of upregulated angiogenesis, enhanced cell motility, and extracellular matrix invasion [78]. In addition, it has been indicated that, in endometrial carcinoma, metastasis and recurrence are closely related with EMT [910].…”
Section: Introductionmentioning
confidence: 99%